A new shock factor of SWATH catamaran subjected to underwater explosion. (15th January 2017) - Guo, Jun; Ji, Xiu-bin; Wen, Yan-yan; Cui, Xiong-wei
Abstract: In order to measure the extreme degree of the impact environment on a SWATH (small waterplane area twin hull) catamaran subjected to an underwater explosion, this work defines a new type of shock factor based on shock wave energy. This new shock factor is used as a parameter to describe the response from this kind of ship, and it is divided into two categories according to characteristics of the SWATH catamaran structure. This research used finite element software to simulate and calculate the response of SWATH catamaran subjected to an underwater explosion. The validity of this new shock factor is proved in three categories, including total kinetic energy, total strain energy and shock spectrum. The results show that the responses of the SWATH catamaran structure are similar when the new shock factor is equal, and it is also appropriate for situations involving short explosive distances. Highlights: ● We have defined a new shock factor of SWATH catamaran subjected to underwater explosion. ● A principle is proposed to replace a complex structure of SWATH catamaran by using double cylinders. ● We derived new formulas for calculation of the shadow area of SWATH catamaran under different conditions.